Peripheral neuropathies in childhood: a neuropathological approach - Chimelli,Leila (1996)
Peripheral neuropathies affect children more often than the young and middle age adults, but less frequently than the elderly. They differ from those in the adults because of the high incidence of hereditary neuropathies, including those associated with metabolic and degenerative disorders of the central nervous system; the low incidence of toxic neuropathies and those associated with systemic disorders; and a lower incidence of chronic acquired polineuropathies. Nerve biopsies are indicated if the diagnosis has not been made with clinical and electrophysiologic studies and other methods, and should only be performed in laboratories with appropriate techniques for the study of the nerve. It is important to know the normal development of the nerve, the thickness of the myelin sheath and the distribution of small and large fibers, according to the age. The main morphological aspects of the most frequent neuropathies in children - acquired (inflammatory, demyelinating) and hereditary (sensory-motor, sensory-autonomic, ataxic, and those associated with metabolic and degenerative disorders), are reviewed.